Youth Labor Force Participation, Education, and Human Capital in Asia, by Gender, 1990-2019 - Barbara M. Fraumeni (Institute of Labor Economics (IZA), 2023)
Of great importance to the future World economy is the future labor force of Asia, as Asia is by far the most populous region in the World. Expected future levels of education, very young and youth population, youth employment and unemployment, dependency rates, human capital per capita, and the sources of growth in the potential future labor force are described in this paper with an emphasis on differences by gender and differences across regions. Some comparisons between China and India and between Asia and selected other regions and aggregates are also included. Gini human capital coefficients are constructed for regions in Asia and the selected other regions and aggregates are constructed to reinforce the importance of recognizing gender in any analysis.
Keywords: I21; J16; J21; J24; O53; 330; labor; education; employment; human capital; Asia